2000
DOI: 10.1021/ic000248p
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Macrocycle Structural Effects on Copper−Dioxygen Reactivity

Abstract: With the goal of understanding how the nature of the tridentate macrocyclic supporting ligand influences the relative stability of isomeric mu-eta 2:eta 2-peroxo- and bis(mu-oxo)dicopper complexes, a comparative study was undertaken of the O2 reactivity of Cu(I) compounds supported by the 10- and 12-membered macrocycles, 1,4,7-R3-1,4,7-triazacyclodecane (R3TACD; R = Me, Bn, iPr) and 1,5,9-triisopropyl-1,5,9-triazacyclododecane (iPr3TACDD). While the 3-coordinate complex [(iPr3TACDD)Cu]SbF6 was unreactive with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
119
2
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 53 publications
9
119
2
2
Order By: Relevance
“…6 However, Tolman and co-workers, 11,13,17,20,21 and later others, [22][23][24][25][26] have demonstrated that in select instances the relative energies of isomeric µ-η 2 :η 2 peroxo and bis(µ-oxo) complexes can be sufficiently close to one another, and the barrier to their interconversion sufficiently low, that the two species may be in rapid equilibrium with one another; theoretical studies have rationalized many of the electronic structural details governing this phenomenon. [27][28][29][30][31][32][33][34] This observation potentially complicates mechanistic analysis in model systems and, by extension, oxytyrosinase, because the kinetics for systems characterized by a rapid preequilibrium can be indistinguishable from systems involving only a single reactant. 35 Thus, even in the absence of observing a spectral signature for a bis(µ-oxo) intermediate, because it is present at, say, part per million concentration, one cannot a priori discount the possibility that this same isomer is so much more reactive than the µ-η 2 :η 2 peroxo that product derives predominantly from prior isomerization and subsequent reaction.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, Tolman and co-workers, 11,13,17,20,21 and later others, [22][23][24][25][26] have demonstrated that in select instances the relative energies of isomeric µ-η 2 :η 2 peroxo and bis(µ-oxo) complexes can be sufficiently close to one another, and the barrier to their interconversion sufficiently low, that the two species may be in rapid equilibrium with one another; theoretical studies have rationalized many of the electronic structural details governing this phenomenon. [27][28][29][30][31][32][33][34] This observation potentially complicates mechanistic analysis in model systems and, by extension, oxytyrosinase, because the kinetics for systems characterized by a rapid preequilibrium can be indistinguishable from systems involving only a single reactant. 35 Thus, even in the absence of observing a spectral signature for a bis(µ-oxo) intermediate, because it is present at, say, part per million concentration, one cannot a priori discount the possibility that this same isomer is so much more reactive than the µ-η 2 :η 2 peroxo that product derives predominantly from prior isomerization and subsequent reaction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, significant chelate-ring-size effects have been found in the copper-dioxygen chemistry, [14,15] catechol dioxygenase reactivity of ironA C H T U N G T R E N N U N G (III) compounds, [16] electrochemical properties of manganeseA C H T U N G T R E N N U N G (III) and (IV) complexes, [17] spectroscopic properties of nickel(II) [18] and cobaltA C H T U N G T R E N N U N G (III) compounds. [19][20][21] Some attempts to consider the effect of chelate cycles size on the spin state of iron(II) have been done in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for O-O activation by copper dimer complexes related to tyrosinase has been the subject of several previous theoretical studies [20,21,22,23,24,25,26]. Most of these studies used ammonia as ligands rather than imidazoles.…”
Section: Introductionmentioning
confidence: 99%